Transcranial colour‐coded duplex of the intracranial large arteries. Issue 4 (15th September 2017) - McKiernan, Sharmaine; Selmes, Christine
Abstract: Transcranial colour‐coded duplex (TCCD) is a non‐invasive ultrasound technique that assesses blood flow within the large arteries of the circle of Willis. In the clinical sonography world, it can be considered a relatively recent technique that is useful to assess cerebral haemodynamics in a variety of conditions. This article covers the anatomy of the circle of Willis, TCCD scanning and information on some common pathologies TCCD may be used to assess. It is important the sonographer is aware of TCCD imaging and of the intricacies involved in the technique.